Accuracy of radiologists, nonradiologists, and laypeople for identifying children with cerebral cortical atrophy from “Mercator map” curved reconstructions of MRIs of the brain - Chacko, Anith; Vedajallam, Schadie; Andronikou, Savvas; Simpson, Ewan; Thai, Ngoc Jade (Indian Journal of Radiology and Imaging, 2020)
Background: Using text reports to communicate bilateral, symmetric, and zonal cortical brain atrophy in children with term hypoxic ischemic injury (HII) to parents and legal professionals contesting compensation rights can be difficult. Using standard cross-sectional images for explaining bilateral, regional brain imaging to laypeople is also challenging. A single flattened image of the brain surface, much like a map of the earth is derived from a globe, can be generated from curved reconstruction of magnetic resonance imaging (MRI) scans, i.e., a Mercator map. Laypeople’s ability to identify abnormal “Mercator brain maps,” without prior training, requires evaluation before use in nonmedical settings. Aim: To determine the sensitivity and specificity of laypeople in detecting abnormal pediatric Mercator flat-earth maps of the brain, without prior training. Methods and Materials: 10 Mercator brain maps were provided to 111 participants individually. The maps comprised 5 HII, 1 cortical dysplasia, and 4 normal cases. Participants were required to identify the abnormal scans. Sensitivity and specificity overall and for participants’ subgroups were calculated. Results: Overall sensitivity and specificity were 67% and 80%, respectively. General radiologists (n = 12) had sensitivity and specificity of 91.2% and 94.6%, respectively. Laypeople (n = 54) had a sensitivity of 67% and specificity of 80%. Conclusion: The high specificity and sensitivity of radiologists validated the technique for distinguishing abnormal scans, regarding cortical pathology. High specificity of laypeople for identifying abnormal brains using Mercator maps indicates that this is a viable communication tool for demonstrating cortical MRI abnormalities of HII in children to laypersons.
Keywords: Cerebral cortical atrophy; curved reconstructions; HII; hypoxic ischemic injury; laypeople; Mercator map; MRI